The Richard Grady Monsplasty: A vertical Z-plasty technique. Issue 4 (August 2021) - Weiss, Dana A.; Steffe, Erin; Borer, Joseph G.; Groth, Travis W.; Roth, Elizabeth B.; Kryger, John V.; Shukla, Aseem R.; Canning, Douglas A.; Mitchell, Michael E.
Summary: Classic bladder exstrophy in the female results in an exstrophic bladder and urethra, an anterior introitus with a bifid clitoris and short labia minora. During closure, the lower abdominal wall is closed and the bifid clitori are brought into close apposition, but are often not completely closed to prevent injury to the clitoral bodies, thus leaving a persistent gap between the clitoral bodies that grows over time. We demonstrate a vertical z plasty closure to provide a 2 layer closure of the mons that decreases tension and improves cosmetic appearance by recreating a clitoral hood that provides a more normal appearance of the external genitalia for girls with bladder exstrophy.